Differential Effects of Temperature and Diet on the Body size-Fecundity Relationship of Aedes albopictus (Diptera: Culicidae) (Bangladesh Journal of Zoology, 2022)
To investigate whether Aedes albopictus females cease reproduction under adverse conditions, they were offered manipulated diets (high and low diets) at 26°C and 28°C. Both of the diets showed a profound effect on development time and body size. Lower temperature and high diet resulted in larger body size, and that further affected fecundity. There was an insignificant relationship between the number of eggs laid and body size excluding high diets at a lower temperature. As fecundity increased with the body size, Ae. albopictus laid more eggs at 28°C under a high diet. Ae. albopictus reserved more eggs at 28°C, however, body size and egg retention were significantly related under a lower diet at 26°C and 28°C. Our findings indicate that the difference in warm temperature and diet condition contributed to fecundity and the results might help in vector.Bangladesh J. Zool. 50 (2): 251-259, 2022